2010
DOI: 10.1149/1.3309674
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the Use of a Thionine/PEDOT Layer as an NADH Electrocatalyst with Applications in Glutamate Sensing

Abstract: The electrochemical properties of a poly(3,4-ethylenedioxythiophene) film doped with the organic dye, thionine are investigated. It is proposed that an interaction is occurring between the Thionine and PEDOT film due to the positive shift of the thionine couple, improved film retention, and the lack of reactive amino groups. The electrocatalytic oxidation of NADH by this modified electrode was also investigated, together with glutamate sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 47 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…Thionine has a tendency to form aggregates in solution if the concentration is too high (Nicotra et al, 2008), which can influence film reproducibility and performance. This approach (a) is based on prior work in our group (Warren et al, 2010) which generated an NADH electrocatalytic layer with subsequent glutamate detection (at glutamate dehydrogenase modified electrodes). Further optimisation of this immobilisation approach was deemed necessary in order to improve thionine loading and uniformity (hence approach (b) as outlined below).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thionine has a tendency to form aggregates in solution if the concentration is too high (Nicotra et al, 2008), which can influence film reproducibility and performance. This approach (a) is based on prior work in our group (Warren et al, 2010) which generated an NADH electrocatalytic layer with subsequent glutamate detection (at glutamate dehydrogenase modified electrodes). Further optimisation of this immobilisation approach was deemed necessary in order to improve thionine loading and uniformity (hence approach (b) as outlined below).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work in our group (Warren et al, 2010) demonstrated that incorporation of nanotubes into the sensor design enhanced performance of the resulting glutamate dehydrogenase biosensor. By modifying MWNT with thionine using an approach similar to that of Wang et al (2007), and then by incorporating them into a preformed PEDOT film (0.1 M sodium p-toluene sulphonate), successful immobilisation of Th-fMWNT onto the electrode surface was achieved.…”
Section: Characterisation Of Thionine-modified Fmwntsmentioning
confidence: 91%
See 3 more Smart Citations